DARI HUTAN ADAT KALAWA KE HUTAN DESA: SEBUAH TERITORIALISASI NEGARA BERBASIS MASYARAKAT? - Yetty Oktayanty (Universitas Andalas, 2014)
This paper aims to examine the process of teritorial rights of village forest through regulation and government policy of Indonesia. Territorialization as governmentality occurs to two processes is becoming customary forest or village forest that is associates with the legal framework and the neoliberal scheme. This paper wants to show how the practices of territorialization at the local level through case studies in Kalawa, Kahayan Hilir Subdistrict, Pulang Pisau District, Central Kalimantan.Territorialization change in forest areas seems especially after the fall of Orde Baru regime. However, territorialization over forests and natural resources in the reform period still going on. Through the above process of territorialization regulation on customary forests and forest villages in four cases the same. First, custumary forest and village forest is part of the state forest. Second, the state has the authority to regulate, even canceling acknowledge customary rights of forest management and forest villages. Three, rights held by customary communities and rural forest communities will be sought so long as not contrary to the interests of the government. Fourth, state is the organization of power all the people at the highest level. Through case studies in Kalawa will show state control through policies and regulations.